LECTURER VOICES TOWARD FUTURE ENGLISH LANGUAGE TEACHING: AUGMENTED REALITY (AR) AND ARTIFICIAL INTELLIGENCE (AI) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
This research was carried out because of the rapid development of the application of English language learning along with the development of technology. The teachers are presented with so many choices of learning applications that are very easy to obtain. In the near future, language learning technology will continue to develop to utilize cutting-edge technology such as Augmented Reality (AR) and Artificial Intelligence (AI).The purpose of this study is to see how the perceptions and understanding of several lecturers in Indonesia related to the development of AR and AI-based learning technology. Then also to see the extent of their support and readiness in concept and application. In the implementation, researchers used a qualitative approach by observing, determining samples, interviewing, studying documents and drawing conclusions.The expected output in this study is to obtain the standard understanding of the lecturers related to the development of learning technology. Thus, there must be a change in the language learning paradigm by developing application-based learning methods. Overall, the results of this study are targeted to be published in a national journal with ISSN. To achieve these targets, this research has been made with a background, conception and objectives that are quite clearly supported with adequate references. Likewise with the methodology and data analysis process that have been used.